Language in crisis negotiations : the Rizal Park hostage-taking incident - Madrunio, Ma. Kaela Joselle Rañosa; Madrunio, Marilu Rañosa (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper is aimed at examining the Rizal Park hostage-taking incident from the lens of forensic linguistics that looks into crime management. The incident happened on August 23, 2010 in Manila, Philippines when a tourist bus loaded with 20 Hong Kong nationals was hijacked by a disgruntled former officer of the Philippine National Police by the name of Rolando Mendoza. Employing the DIAMOND model of Grubb et al. (2020), FBI’s Behavioral Change Stairway Model (BCSM), and Hammer’s (2007) S.A.F.E. model, the study analyzed the stages in the negotiation process employed by the negotiators, the relationship-building process and the communicative dynamics of the hostage-taking incident. Findings revealed that the stages of negotiation in the DIAMOND model were not all carried out. Following the BCSM model, the negotiators were not able to build empathy with the hostage-taker. Communicative dynamics as reflected in the S.A.F.E. model was not likewise successful as pertinent information was not transmitted with maximum effectiveness. The poor handling of the incident and the failure of the negotiation led to the eventual death of innocent people, including the hostage-taker himself and the issuance by the Hong Kong government of a ‘black’ travel alert for the Philippines. It is hoped that with this study, a more effective and efficient way of managing crime incidents in the country can be carried out to avoid further disasters.